Power Decreases Loneliness through Enhanced Social Support: The Moderating Role of Social Exclusion - Sun, Gong; Wang, Wangshuai; Han, Jianyi; Yu, Zucheng; Li, Jie (Anales de Psicología / Annals of Psychology, 2021)
In recent years, power and loneliness are two important research topics in social psychology. However, they are in separate streams of literature despite the potential relationship. To fill this gap, this research systematically investigates how, why, and when sense of power affects loneliness by examining the main effect, the mediating role of perceived social support, and the moderating role of social exclusion. In Study 1, 539 participants in China participated in a survey study, which included Sense of Power Scale, Perceived Social Support Scale, and UCLA Loneliness Scale. In Study 2, we casually tested the main and moderating effects in a controlled experiment using a sample from the United States. Taken together, the results show that: (1) Sense of power reduces loneliness. (2) Perceived social support mediates this relationship, such that power enhances perceived social support and thereby decreases loneliness. (3) Social exclusion moderates this relationship, such that the buffering function of power is effective only when social exclusion is absent.